Small ruminant value chain and empowerment: a gendered baseline study from Ethiopia - Kinati, Wole; Temple, Elizabeth C.; Baker, Derek; Najjar, Dina (Frontiers in Sustainable Food Systems, 2023)
Despite growing interest in gender analysis in value chains, comparatively few studies have analyzed gender relations in small ruminant value chains using sex-disaggregated quantitative data in livestock-based systems. This study, drawing on baseline data from the Small Ruminant Value Chain Development Program (SRVD) in Ethiopia, aims to address two research questions: what is the gender status along small ruminant value chain stages and the related associations among aspects of empowerment and socio-economic variables? Building on multiple empowerment and value chain frameworks, our findings reveal that small ruminant market participation, related decisions, and control over income, are gender differential. Estimation results identified several variables significantly associated with agency dimensions, achievements, or both, with mixed results. These are age group, context, being married, being men and head of household, participation in breeding stock selection, livestock ownership, contact with extension agent, access to market information, and participation in selling at market places. Participation in small ruminant value chain may encourage more egalitarian decision-making behaviors but does not guarantee the capacity to make autonomous decision-making, and thus needs to be coupled with interventions on empowerment dimensions. Nevertheless, further investigations are required in order to establish the mixed results with additional variables on norms.